(untitled) (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Stigma and unfavorable view of people towards mental illness is prevailing in Nepal due to lack of awareness. Stigma among family members of people with mental illness has a serious impact on the outcome. This study aims to identify the level of perceived stigma by family members and association with selected demographical variables. Methods: A cross-sectional research design was used to assess the stigma perceived by family members of patients visiting psychiatry outpatient department of Patan Hospital, Patan Academy of Health Sciences during 12 August to Sep 7, 2018. Questionnaire on socio-demographic variables and self-stigma of mental illness scale was used to interview the family members to assess the level of perceived stigma. Chi-square was used to examine the association between demographic variables and stigma, p < 0.05 was considered significant. Results: Out of 180 family interviewed 94 (52.2%) had perceived high level of stigma and 86 (47.8%) low level of stigma. There was significant association between age and perceived stigma (p value=0.030) at 95% of significance. Conclusions: More than half of the family members of psychiatric patients had perceived high level of stigma and was associated with the age.